IMPLEMENTASI PENDEKATAN HEUTAGOGI: SELF-DETERMINED LEARNING UNTUK CALON GURU SD/MI - Hikmah, Afroh Nailil; Chudzaifah, Ibnu; Rohman, Wahyudi Agung (Jurnal As Sibyan, 2024)
This research aims to implement a heutagogical approach, or self-determined learning, in the educational process of prospective elementary school (SD) and Madrasah Ibtidaiyah (MI) teachers. The heutagogical approach places prospective teachers at the center of learning, allowing them to take the initiative in designing and managing their own learning processes. This research uses a qualitative method with a case study approach, where data is obtained through observation, interviews and document analysis related to the heutagogy-based learning process. The research results show that this approach is successful in increasing the motivation and involvement of prospective teachers in the learning process, as well as encouraging the development of critical, creative and reflective thinking skills. The implementation of heutagogy also helps prospective teachers to be more adaptive and responsive to changes in the educational context, as well as equipping them with the ability to continue learning and developing throughout their careers as educators. Other findings show that prospective teachers who are involved in heutagogy-based learning are able to develop more personalized and relevant learning methods, which not only increase their understanding of the material, but also their readiness to face challenges in the field. Overall, this research concludes that the heutagogical approach is an effective strategy in preparing prospective elementary/MI teachers to become independent, innovative and competent educators. By adopting this approach, educational institutions are expected to be able to produce teachers who are not only able to teach well, but also have the skills to continue to adapt and develop in facing the ever-changing dynamics of the world of education.